ALLOCATION OF VILLAGE FUNDS FOR EMPOWERMENT IN THE BORDERLAND AREA - Rissa Ayustia; Veneranda Rini Hapsari (Proceeding International Conference on Information Technology and Business, 2018)
The allocation of village funds from the central government whose numbers have increased every year is expected to empower the community, especially in borderland area through economic independence (Case Study of Seren Selimbau Village, Lumar District, Bengkayang Regency). This study is intended to determine the extent to which Village Fund Allocation in contributing to the empowerment in borderland area as well as problems of irregularities in the management and use of village funds encountered for evaluation and solutions. Until now, the central government's concern for the development in borderland area is the use of funds for the construction of physical infrastructure and not yet fully for community empowerment . This research location in Seren Selimbau Village, L umar District, Bengkayang Regency. Data collection techniques in this study using interview, observation and documentation techniques and analyzed qualitatively. Field research in the form of observation, in-depth interviews and document research. The resource person in this study was the Seren Selimbau Village Community , Lumar Sub-district Head, Seren Selimbau Village Chief , Secretary Seren Selimbau Village , Treasurer Seren Selimbau Village, Village KAUR, Head of Government Affairs , District and Village Assistants . Data analysis is carried out by means of data collection, data reduction, data presentation, and conclusion drawing or data verification. This study uses qualitative data analysis methods with objectives in order to get a comprehensive picture of village fund allocation for empowerment of border communities (Case Study of Seren Selimbau Village, Lumar District, Bengkayang Regency).Keywords: Village Fund Allocation , Community Empowerment